2023
DOI: 10.3390/electronics12030570
|View full text |Cite
|
Sign up to set email alerts
|

2D-Nanolayer (2D-NL)-Based Hybrid Materials: A Next-Generation Material for Dye-Sensitized Solar Cells

Abstract: Two-dimensional (2D) materials, an electrifying family of innovative materials, have recently attracted wide attention due to their remarkable characteristics, primarily their high optical transparency, exceptional metallic conductivity, high mechanical strength, carrier mobility, tunable band gap values, and optimum work function. Interestingly, 2D-nanosheets/nanolayers (2D-NLs) might be synthesized into single/multi-layers using simple processes such as chemical vapor deposition (CVD), chemical bath depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 137 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…CB-2D-Ms can provide mechanical flexibility together with large surface area and pore size distribution. [14][15][16][17][18][19][20][21][22][23][24][25] Additionally, several studies have shown that CB-2D-Ms can effectively inhibit the growth of various bacteria, including Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), and Pseudomonas aeruginosa (P. aeruginosa). Usually, their antibacterial activity can be attributed to various mechanisms, such as disruption of bacterial cell membranes, oxidative stress, and inhibition of bacterial adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…CB-2D-Ms can provide mechanical flexibility together with large surface area and pore size distribution. [14][15][16][17][18][19][20][21][22][23][24][25] Additionally, several studies have shown that CB-2D-Ms can effectively inhibit the growth of various bacteria, including Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), and Pseudomonas aeruginosa (P. aeruginosa). Usually, their antibacterial activity can be attributed to various mechanisms, such as disruption of bacterial cell membranes, oxidative stress, and inhibition of bacterial adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…One important characteristic of semiconductors is crystallite size, which affects electron transport properties within the semiconductor [ 11 , 12 ]. Furthermore, device performance can be improved via dopant addition, which improves the electron transport properties [ 13 ]. For example, doping with graphene oxide can improve electron transfer properties in DSSC [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, various carbon forms, carbon nanotubes, graphite, graphene, graphene doped with oligothiophene [ 44 ], and materials such as 2D-Nanolayer (2D-NL)-Based Hybrid Materials (either electron-transport layers (ETLs) or hole-transport layers (HTLs)), can also be used in dye-sensitized solar cells (DSSCs). However, they present some drawbacks, such as low stability and a low photo conversion efficiency (PCE), because the stability of these materials is one of the major challenges following the development of DSSCs [ 45 ].…”
Section: Introductionmentioning
confidence: 99%